Premature Ejaculation Among Italian Men: Prevalence and Clinical Correlates From an Observational, Non-Interventional, Cross-Sectional, Epidemiological Study (IPER) - Verze, Paolo (Sex Med, 2018)
INTRODUCTION: There is a great variability in the prevalence of premature ejaculation (PE) worldwide and only few data are available about the Italian population. AIM: To determine the prevalence of PE in the adult male population in Italy. METHODS: Adult men 18 to 80 years old who were sexually active were randomly sampled from patient lists of general practitioners in Italy and were included in this observational, non-interventional, cross-sectional epidemiologic study from January to July 2015. MAIN OUTCOME MEASURES: Subjects were asked to complete general questionnaires on anthropometric data, lifestyle, education, occupation, economic conditions, general health status, comorbidities, and sexual habits: the Premature Ejaculation Diagnostic Tool (PEDT), the 5-item International Index of Erectile Function, and the Sexual Quality of Life Questionnaire–Male. RESULTS: 1,104 subjects were recruited. Mean age was 45.6 years. Mean prevalence of PE based on PEDT score (≥11) was 18.5%, and 12.4% self-reported an intravaginal ejaculatory latency time shorter than 1 minute. Prevalence of PE proportionally increased with age. 64.6% of patients presented lifelong PE vs 35.4% of patients who reported acquired PE. Estimated prevalence of coexisting PE and erectile dysfunction was 7.0%. Furthermore, overall quality of sexual life was significantly worse in men with PE (P = .006). Enrolled men reported an overall rate of sexual problems in their partners of approximately 30%. 31.3% of patients with PE did not seek help for their dysfunction. No significant differences were noted between patients with and without PE for body mass index, alcohol consumption, smoking habits, physical activity, education, economic conditions, and marital status. CONCLUSIONS: PE has a high prevalence in the Italian male population, increases with age, and heavily affects quality of life in patients and their partners. Encouraging data exist concerning the percentage of patients seeking help for their condition. Verze P, Arcaniolo D, Palmieri A, et al. Premature Ejaculation Among Italian Men: Prevalence and Clinical Correlates From an Observational, Non-Interventional, Cross-Sectional, Epidemiological Study (IPER). Sex Med 2018;6:193–202.